First report of albinism in vizcacha Lagidium viscacia (Rodentia: Chinchillidae) in Peruvian Andes - Pelaez-Tapia, Yulina (2021)
We report the first record of albinism in vizcacha (Lagidium viscacia) based on two adult individuals sighted in department of Apurímac, in Peru. This record represents the first report of albinism in Chinchillidae.